Knowledge, attitudes and beliefs of Turkish women towards blood donation - (:unkn) unknown (PAKISTAN MEDICAL ASSOC, 2014)
Objectives To understand the knowledge attitudes and beliefs of women towards blood donation and to help healthcare workers to plan steps to increase blood donation rates Methods The qualitative study was conducted between January to May 2013 in two densely populated districts of Istanbul Turkey that are inhabited mostly by socio economically disadvantaged people from different parts of the country The area also serves as the Research and Training Area of the Marmara University Results There were 57 women subjects in the study with an age range of 18 65 years There were positive attitudes towards blood donation although none of the women in our sample had donated blood before All the participants (100%) thought that men could donate blood but it was not favourable for the women since they were already losing blood through menstruation The circumstances surrounding women such as being too busy and overloaded with caring of the family belief of impurity of female blood suspicion of having unhealthy blood rumours misbeliefs and negative experiences anxiety about the procedure (fear of needle fear of syncope) and distrust of blood banks were the other reported barriers Conclusion Understanding the factors that motivate donors and presenting issues like rumours misbeliefs and negative experiences will facilitate improvement in blood banks and eventually help increase the donation rates
Keywords: Blood donation; Turkey; Qualitative; Voluntary; DONORS; MOTIVATIONS